A Review Study of Psychometric Functioning of a Picture Scale to Assess Joy in Childhood - Oros, Laura Beatriz (2015)
The early emergence of emotional understanding by means of facial expressions allows the assessmentof basic emotions from young ages through pictures or photographs of human faces. Thisevaluation strategy allows children, with limited language to reveal feelings that neither investigatorsnor clinicians would be able to obtain verbally. The present work presents a non-verbal activityaimed at testing children?s joy. It is based on a visual analogue scale integrated by sevenpictures of infant facial expressions. This scale has the advantage of presenting an animated design,more friendly and appealing than simplified face scales. Its psychometric functioning, revisedfrom different studies, demonstrates that it is a reliable and valid alternative to analyze the experienceof joy in small children.